The practice of leadership in higher education : real-world perspectives on becoming, being and leaving - Jarrett, Kendall; Newton, Stephen (London ; New York, NY : Routledge/Taylor & Francis Group, 2021)
"This practice-orientated book explores the nature of leadership in higher education during three key stages of the leadership cycle: becoming, being and leaving leadership. Providing perspectives on leadership from a range of professional sectors this book presents considered views on contemporary and future leadership practices in higher education from a global network of contributors. Included within each chapter are prominent questions designed to engage the reader to think about their own leadership experiences to date and leadership development needs. Key points covered include: The complexities of leadership in higher education in a changing world, Discussion of internally resourced leadership development frameworks and programmes currently used across the sector, Leading complex education systems, Perspectives on leadership from a range of professional sectors such as corporate, military, elite sport, and public, that can be used to improve the quality of higher education leadership Case studies of academics' leadership practices that provide readers with authentic personal insights into discipline specific leadership experiences from around the world Full of practical examples of personal leadership experiences which can be used to help inform readers' leadership aspirations, development and legacy planning, this is the ideal read for anyone interested in understanding their identity and practice as a leader in higher education"--
Includes index.
Keywords: Education, Higher -- Administration; Universities and colleges -- Administration; Educational leadership; Education and globalization